Permanent electronic identification of Alentejano swine breed animals - Tirapicos Nunes J.; Paiva J.C.; Almeida J.A. (Tradition and innovation in Mediterranean pig production, 2000)
Traditional dry cured products protected with (POD or GI) must be authenticated in order to create confidence at consumers' level. Permanent electronic identifications are the best method of identifying living animals. This work aimed at extending the identification across the whole production and food processing chains, until this product reaches the consumer. Microchips were placed at hock level into 48 piglets at weaning, 24 alentejano pure breed and 24 alentejano crossed with Large-White (LW). Animals were raised outdoors. At plus minus 100 kg of live weight, hogs were slaughtered under standard conditions at Beja slaughterhouse. Refrigerated carcasses were sent to Barrancos town, where they were took to pieces. Sixteen hams from identified pigs were processed according to local tradition (salting circa 7 days, cool post-salting approximately 35 days and natural long dry period). Two transponders were lost during the growing phase of pigs. Twelve months after processing of hams, microchips were still working.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)